EXPLORING STUDENTS’ DIFFICULTIES IN WRITING PROCEDURE TEXTS: INSIGHTS FROM SMA AISYIYAH 1 PALEMBANG - Sulfa Aprillia; Roma Nur Asnita; Hariana Amalia (Didascein : Journal of English Education, 2025)
This study aimed to find out the difficulties encountered by the students in writing procedure texts at SMA ‘Aisyiyah 1 Palembang. Writing is often considered a productive and crucial skill for students' future, yet many learners find it difficult to master due to complex components such as vocabulary, grammar, and sentence structure. This study applied qualitative research with a case study design to investigate the specific phenomena of student challenges in depth. The participants of this study were seven students from the tenth grade, selected by using a purposeful sampling technique, specifically homogeneous sampling. Semi-structured interviews were conducted to collect the primary data, which were then analyzed by using the thematic analysis procedure. The research findings revealed that there were five major difficulties faced by the students in writing procedure text. These difficulties included grammatical problems, specifically in determining pronouns, and mechanical problems such as deciding the right spelling for unfamiliar words. Additionally, students struggled with sentence structure when arranging the steps of the procedure, and faced psychological barriers, including a lack of self-confidence and significant writing anxiety. Problems with the generic structure of the text were also identified. In brief, the tenth-grade students still face diverse challenges in writing, and it is recommended that they improve their comprehension and skills in this specific genre.